USO DE ÁGUAS RESIDUÁRIAS DE SUINOCULTURA COMO MEIO DE CULTURA ALTERNATIVO NO CULTIVO DE Scenedesmus obliquus (Turpin) Kützing VISANDO A PRODUÇÃO DE BIOCOMBUSTÍVEL - Silva, Laiza Cristina Ricatto da (2020)
Swine is an important activity for the economy, being Brazil one of the largest pork producers in the world. However, such activity requires excessive use of freshwater to clean the nurseries, generating a large amount of wastewater, if without proper tre